Characterization and modulation of glucose uptake in human blood-brain barrier model - Meireles, Manuela (2013)
The blood-brain barrier (BBB) plays a key role in limiting and regulating glucose access to glial and neuronal cells. In this work glucose uptake on a human BBB cell model (the hCMEC/D3 cell line) was characterized. The influence of some hormones and diet components on glucose uptake was also studied.